Tingginya Uang Hantaran terhadap Penundaan Perkawinan di Desa Aek Nabara Jae Kec Aek Nabara Barumun Kab Padang Lawas - Etti Uliana Hasibuan (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Remittance money is a number of cost contributions given from the groom-to-be to the prospective in-laws to meet the needs of the wedding. The tradition of money delivery in the culture of the Mandailing Angkola community, especially in Aek Nabara Jae Village, is a symbol of the bride-to-be's seriousness towards the woman. However, in practice, this tradition often causes problems when the nominal amount set exceeds the reasonable limit. Too high a dowry has caused many couples, especially from the lower middle economic class, to be forced to postpone their marriage. This research aims to examine the implementation and determination of remittances in local wedding customs, as well as how Islamic law views these conditions. This study uses a qualitative-descriptive method through field observation and interviews. The results of the study showed that the determination of remittance money was influenced by education level, social status, and the intervention of extended families. In the view of Islamic law, the determination of the dowry that burdens and hinders marriage is contrary to the principle of convenience and benefit in muamalah.